2010
DOI: 10.1007/s11663-010-9424-y
|View full text |Cite
|
Sign up to set email alerts
|

Exergy-Based Efficiency Analysis of Pyrometallurgical Processes

Abstract: Exergy based efficiency analysis provides a powerful tool for optimizing industrial processes. In this paper, the use of this technique for pyrometallurgical applications is explored in four steps.First, the exergy concept is introduced, the outline of exergy calculations is presented and the role of a reference state is discussed. Second, it is shown that an unambiguous exergy calculation for pyrometallurgical streams with a complex, unknown phase composition is not straightforward.Hence, a practical methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Exergy analyses of two industrial furnaces showed overall exergy efficiencies of 0.30 (ferro-silicon furnace) [20] and 0.33 (silicon furnace) [21]. A direct comparison was not feasible, as this requires that a consistent methodology is applied [13]. A large potential for additional power production from thermal energy in the off-gas was documented.…”
Section: Introductionmentioning
confidence: 99%
“…Exergy analyses of two industrial furnaces showed overall exergy efficiencies of 0.30 (ferro-silicon furnace) [20] and 0.33 (silicon furnace) [21]. A direct comparison was not feasible, as this requires that a consistent methodology is applied [13]. A large potential for additional power production from thermal energy in the off-gas was documented.…”
Section: Introductionmentioning
confidence: 99%
“…58 Drielsma et al, 2016;Ignatenko et al,, 2007;Klaasen et al, 2010;Norgate y Haque, 2010;Norgate y Jahanshahi, 2010;Norgate et al, 2007;Rankin 2017) la necesidad de implementar análisis de ciclo de vida y otras estrategias, para tener indicadores no solo técnicos sino también socioeconómicos y ambientales que permitan tener un mejor entendimiento de la problemática asociada al tratamiento de minerales a pequeña y gran escala.…”
Section: Discussionunclassified
“…6. This trend indicates the usefulness of exergy to determine how a pyrometallurgical process can occur efficiently [12]. Because of this, it is possible to relate the exergy associated to copper converting with the concentration of SO 2 in the off-gases; this is illustrated in Fig.…”
Section: Exergy Associated To Copper Conversionmentioning
confidence: 98%